2014
DOI: 10.1007/s11104-014-2074-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar amendment on root traits and contaminant availability of maize plants in a copper and arsenic impacted soil

Abstract: Biochar has been proposed as a tool to enhance phytostabilisation of contaminated soils but little data are available to illustrate the direct effect on roots in contaminated soils. This work aimed to investigate specific root traits and to assess the effect of biochar amendment on contaminant availability. Amendment with two different types of biochar, pine woodchip and olive tree pruning, was assessed in a rhizobox experiment with maize planted in a soil contaminated with significant levels of copper and ars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 30 publications
5
39
1
2
Order By: Relevance
“…In the higher doses of BC plants showed more developed and distributed roots (data not shown). Phytoremediation combined with BC addition to soil can enhance soil biological activity (Lu et al, 2015) because BC amendment promotes root growth (Brennan et al, 2014).…”
Section: Impacts Of Bc On Plants and Soilmentioning
confidence: 99%
“…In the higher doses of BC plants showed more developed and distributed roots (data not shown). Phytoremediation combined with BC addition to soil can enhance soil biological activity (Lu et al, 2015) because BC amendment promotes root growth (Brennan et al, 2014).…”
Section: Impacts Of Bc On Plants and Soilmentioning
confidence: 99%
“…Brennan et al (2014b) showed an increase in maize (Zea mays) biomass and chlorophyll content after biochar produced form pine woodchip and maize stubble was added to soils contaminated with PAHs, As, Cu, and Zn. Furthermore, biochar promoted the development of fine maize roots, crucial to water and nutrient uptake in Cu-and As-contaminated soil (Brennan et al, 2014a). Houben et al (2013a) found that the availability of Cd, Zn, and Pb to Brassica napus decreased with increasing biochar applications.…”
Section: Plantsmentioning
confidence: 99%
“…Biochar potentially can prevent leaching of pollutants from compost. The addition of biochar can reduce leaching of nitrate from soil (Knowles et al, 2011;Clough et al, 2013) and reduce pore water concentrations of metals (Brennan et al, 2014;Meng et al, 2014). Dissolved organic matter, however, can negate the increased sorption of metals by biochar (Beesley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%